Pengaruh Katekese Model Shared Christian Praxis (SCP) terhadap Partisipasi Aktif Orang Muda Katolik Di Lingkungan Santo Yohanes De Brito Paroki Santo Yosep Bambu Pemali - Dedimus Berangka; Eltina Devonsa (JURNAL PASTORAL KATEKETIK, 2025)
Young Catholics are an essential part of the Church with responsibilities in the development and renewal of the Church. This research aims to analyze the influence of the Shared Christian Praxis (SCP) catechesis model on the active participation of young Catholics in Santo Yohanes De Brito Community, Santo Yosep Bambu Pemali Parish. The research used a quantitative approach with a regression analysis model. The research sample consisted of 60 young Catholics with data collection using questionnaires. The results showed that (1) there is a significant influence of the SCP catechesis model on the active participation of young Catholics with a significance value of 0.000 < 0.05; (2) the contribution of the SCP catechesis model to the active participation of young Catholics is 97%, while 3% is influenced by other variables not examined; (3) solutions that can be used to increase the active participation of young Catholics are by increasing cooperation between parents, community leaders, parish priests, and members to organize programmed youth activities. This research provides important implications for developing effective faith formation models for young Catholics to increase their active participation in church life.